Altered spontaneous brain activity patterns in patients with neovascular glaucoma using amplitude of low‐frequency fluctuations: A functional magnetic resonance imaging study - Zhi‐You Peng; Yu‐Xin Liu; Biao Li; Qian‐Min Ge; Rong‐Bin Liang; Qiu‐Yu Li; Wen‐Qing Shi; Ya‐Jie Yu; Yi Shao (Brain and Behavior, 2021)
Abstract Background Neovascular glaucoma (NVG) can cause irreversible visual impairment and abnormal spontaneous changes in brain's visual system and other systems. There is little research on this aspect at present. However, amplitude of low‐frequency fluctuations (ALFFs) can be used as an rs‐fMRI analysis technique for testing changes in spontaneous brain activity patterns. Purpose The aim of this study was to probe the local characteristics of spontaneous brain activity in NVG patients and analyze their correlation with clinical behaviors. Methods Resting‐state functional magnetic resonance imaging (rs‐fMRI) scans were obtained from eighteen patients with NVG (8 males, 10 females) and eighteen healthy controls (HCs; 8 males and 10 females) who were matched in age, gender, and education level. We evaluated spontaneous brain activity with the ALFF method. A receiver operating characteristic (ROC) curve was used to compare the average ALFF values for altered brain regions of NVG patients with those of HCs. Results Compared with HCs, NVG patients had lower ALFF values in the right cuneus, right middle occipital gyrus, left cingulate gyrus, right precuneus, and left medial frontal gyrus (p < 0.001). Higher ALFF values were observed in the right superior frontal gyrus and left middle frontal gyrus (p < 0.001). Analysis of the ROC curves of the brain regions showed that the specificity and accuracy of ALFF values between NVG and HCs in the area under the curve were acceptable (p < 0.001). Conclusion The patients with NVG exhibited anomalous spontaneous activity in different brain regions; these finding should establish the foundation for a more comprehensive understanding of the pathological mechanisms of NVG. Furthermore, these abnormal variations in specific brain regions can be considered possible clinical indices of NVG.